In Vitro-In Vivo Characterization of Oleuropein loaded Nanostructured Lipid Carriers in the Treatment of Streptococcus pneumoniae induced Meningitis - Reddy, Dr. K. Bhaskar (Asian Journal of Pharmaceutics (AJP), 2019)
Background: Olive leaf, a versatile plant obtained from Olea europaea which was enriched with various secondary metabolites likes polyphenols, secoirodiods eg. Oleuropein, Hydroxytyrosol etc. Current treatment modalities for meningitis were ended up with MDR. Hence, a new strategy is mandate to alleviate bacterial meningitis. Objective: Current research structured to identify the potential of Oleuropein loaded NLC in the inhibition of Bacterial Meningitis. Glycerol is used as bio-solvent in hot blanching assisted microwave extraction & extracts were analyzed by using UV, FTIR, HPTLC and HPLC to quantify the Oleuropein. Methodology: NLC was formulated by melt dispersion ultrasonication method using Box-behnken design. Formulated NLC was analyzed for particle size, zeta potential and in-vitro drug release studies. Toxicity and Histo-pathological examination was done in albino Wistar rats using cerebellar cistern puncture method to estimate In-vivo potential of Oleuropein in bacterial meningitis. Results and Discussion: From the data, it was observed that hot blanching process potentiates the extraction and the data depicts that aqueous glycerol extract contain huge amount of Oleuropein. Optimized NLC resides with 165nm of size, ZP of -40mv and PDI of 0.3 with a sustainable release of drug for 12hrs. By Histo-pathological examination, regeneration of brain tissue was initiated in the hippocampus region in treated group as compared to control group. Conclusion: Combination of hot blanching with microwave extraction for Oleuropein and subsequent loading of drug into NLC shown significant positive effect on treatment of Streptococcal meningitis.